MEMBANGUN SENDIRI SISTEM INFORMASI LABORATORIUM - Yogi Sucahyo; Supri .; Prihatini . (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2008)
LIS (Laboratory Information System) include software, hardware and brain ware. It could accepted the laboratoryinformation’s,analyze and organize the activity clinical laboratory The laboratory information system confirm laboratory’s businessfrom input and output process According this Semen Gresik Hospital was increase the quality of clinical laboratory information. TheLIS needs computers as workstations, instrument interface server, as well as laboratory automation systems. The recorded ID barcodelabels used for patients identification as well as for administration and labeling the samples. The samples were process (analyses) andthe results were printout. LIS will decrease the patients’ turn around time as well as the praeanalytic errors. The self-building of LIS ischeaper than the laboratory instruments bought including.